2017
DOI: 10.3892/ol.2017.6255
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as outcome predictors in patients with metastatic colorectal cancer treated with bevacizumab in combination with FOLFOX

Abstract: Bevacizumab is a humanized anti-vascular endothelial growth factor monoclonal antibody, used in combination with a oxaliplatin-based chemotherapy in the treatment of metastatic colorectal cancer (mCRC). The aim of the present study was to identify microRNA (miRNA)-based predictive biomarkers of therapy response in order to avoid unnecessary and costly therapy to non-responding patients. High-throughput miRNA microarray profiling (Affymetrix miRNA array) was performed on a discovery cohort of patients with mCRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…These data showed that overexpressing Furthermore, miR-125a-5p has been validated to prevent the cancer cell progression. [10][11][12][13][14][15][16][17][18][19]23,24 However, the underlying mechanism of the low expression of miR-125a-5p in gastric cancer remains unknown.…”
Section: Overexpressing Mir-125a-5p Suppresses Gastric Cancer Develmentioning
confidence: 99%
“…These data showed that overexpressing Furthermore, miR-125a-5p has been validated to prevent the cancer cell progression. [10][11][12][13][14][15][16][17][18][19]23,24 However, the underlying mechanism of the low expression of miR-125a-5p in gastric cancer remains unknown.…”
Section: Overexpressing Mir-125a-5p Suppresses Gastric Cancer Develmentioning
confidence: 99%
“…Studies have demonstrated a role for miRNAs in resistance or sensitization of tumors to chemotherapy and radiotherapy. Previous studies have looked at miRNA´s role as predictors for antiangiogenic therapy by comparing their expression in responders vs. nonresponders either before or after treatment (Kiss et al , ), or changes in the level of circulating miRNAs (Hansen et al , ). The present study is, to our knowledge, the first study to address the changes in miRNA expression within the tumor over the course of treatment, and their correlation to response.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have also been shown to have pro‐angiogenic effects (i.e., the miR‐17‐92 cluster (Suarez et al , ), miR‐21 (Liu et al , ), and miR‐378 (Lee et al , )) or antiangiogenic effects (i.e., miR‐221 and miR‐222 (Poliseno et al , )). Studies in colorectal cancer, glioblastoma, and ovarian cancer have identified miRNAs with potential as predictors for antiangiogenic therapy by comparing expression levels in responders vs. nonresponders in surgical resections from the primary tumor before or after treatment (Chan et al , ; Hayes et al , ; Kiss et al , ). Changes in circulating miRNAs have also been assessed, where miR‐126 has been shown to predict response in patients with metastatic colorectal cancer during chemotherapy and Bev treatment (Hansen et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…miR-92b-3p, miR-3156-5p, miR-10a-5p, and miR-125a-5 were found to be related with progression-free survival in meta;static CRC patients treated with 5-FU/oxaliplatin/bevacizumab regime [90]. A negative relationship was found between miR-27b, miR-148a, and miR-326 expression levels and progression-free survival in metastatic colorectal cancer patients receiving first-line oxaliplatinbased treatment [91].…”
Section: Chemotherapymentioning
confidence: 95%